Pengaruh Green Accounting, Corporate Social Responsibility (CSR), Dan Reputasi Perusahaan Terhadap Kinerja Keuangan - Hidayati, Annisa; Rosidi, Rosidi (Jurnal Riset Akuntansi, 2024)
This study aims to examine the effect of green accounting, corporate social responsibility (CSR), and firm reputation on financial performance. The population in this study consists of all manufacturing and mining companies listed on the Indonesia Stock Exchange in 2021–2022, from which the samples of 54 companies are selected through purposive sampling. This study involves secondary data of the annual reports and sustainability reports obtained from the companies’ official websites. The variables of green accounting, firm reputation, and financial performance are represented by environmental costs, market-to-book value ratio, and return on assets, respectively. The data are analyzed by multiple linear regression processed SPSS version 26. The analysis results exhibit that green accounting has a negative effect on financial performance while CSR and firm reputation have a positive and significant effect on financial performance.